A linguagem dos quadrinhos na mediação do ensino de geografia: charges e tiras de quadrinhos no estudo de cidade - Silva, Eunice Isaias da (2010)
This work has the results of an investigation on the possibility of studying scholar geographic contents through the mediation of comics and comic strips. Based on the presuppose that several knowledge of the urban/city space dynamic represented on these cultural products can motivate the critical debate, it was defined the goal to reflect about the potential of such images and discourses to consolidate concepts related to the geography of the city, theme which is present through every level of the elementary school. The proposal is, thus, to contribute to the Geography teaching, especially concerning the conception of importance of the geographic knowledge to live the everyday of the city. It was selected to this research comic strips from the book Toda Mafalda, by the Argentinean Quino, as well as comics and comic strips by the Brazilian cartoonists Jorge Braga and Mariosan, and also comics of the character Katteca, created by João Luis Brito de Oliveira, known as Britvs, published in the newspaper O Popular, from Goiânia, Goiás. The criterion of selection was the presence of elements which could be articulated to the geography teaching of the city and the material selected was organized according to four thematic axes: places in the city and citizenship; city, consumption and citizenship; city, the habitat and citizenship; urban environment and citizenship. The procedure was “participant observation” in geography classes with students from a public school in Goiânia, in which were used comics and comic strips chosen to mediate the construction of geographic concepts related to the study of the city, in order to produce meaningful knowledge for the students. The approached learning process presupposes the elaboration of knowledge by active subjects, having the dialog as a mean of communication, without prerequisite to the knowledge acquisition, in a way that the meanings are articulated in a non-linear way, without hierarchy among them, forming a net of meaning which inter-crosses itself, constituting knots (concepts or meanings). Based on this paradigm, it was done, upon the orientation of the researcher-professor, activities of scholar learning, in Geography classes of elementary school, with the goal of producing geographic knowledge through the metaphor of the net of meaning, using this daily language to elaborate the hypertext, a text crossed by dialogic information of several texts and voices. An activity with a similar dynamic was done, in a workshop format, in a scientific-academic event. The reached results provided the understanding that the use of this alternative language is able to consistently form geographic concepts. It was concluded that this cultural production constitute a source of didactic-pedagogical resources to the process of teaching-learning of Geography, making this science more accessible and meaningful to the students, by making the necessary articulation between the scientific production and the living world. Appendix B chains together the comics and comic stripes, the activities developed in the experience of participant observation, as well as the photographic documentation of this study.